Sistem e-learning berbasis web pada SMA Negeri 1 Sungai Rumbai: Indonesia - Tifani Tifani (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2021)
As a high school that continues to grow in Dharmasraya, SMA Negeri 1 Sungai Rumbai is a high school located on Jalan Tuanku Kingdom Sungai Rumbai, Sungai Rumbai sub-district, Dharmasraya district, West Sumatra province, with a total of 518 students in the 2020/2021 academic year. This school is still carrying out the conventional learning process, in other words that the teaching and learning process between students and teachers can only be carried out on the condition that there is a meeting between students and teachers in the classroom. If the meeting between students and teachers does not occur, then the learning process will automatically be hampered and the limited time for teaching and learning in the classroom sometimes prevents teachers from providing all learning materials to students. This is a problem for students and teachers who want to convey in detail about the learning. To facilitate the teaching and learning process at SMA Negeri 1 Sungai Rumbai, the author wants to build a web-based electronic learning system, namely an e-learning system using a web-based programming language, PHP, and Mysql database so that students and teachers can connect to each other using the computerized learning system. . Keywords: E-learning, Web, PHP, and MySql